2018
DOI: 10.1071/py17084
|View full text |Cite
|
Sign up to set email alerts
|

Australian general practitioners' perspective on the role of the workplace Return-to-Work Coordinator

Abstract: General practitioners (GPs) play a key role in the return-to-work process, and yet their experiences working with workplace Return-to-Work Coordinators (RTWCs) have rarely been studied. The aim of this paper is to provide insights from the GP perspective about their experiences with workplace RTWCs and their preparedness for the role. GPs from Australian states and territories where legislation mandates workplaces employ a RTWC were requested to complete a questionnaire on their experiences with workplace RTWC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The need for relevant knowledge is included in the domain "characteristics of individuals" and the construct "knowledge and beliefs about the intervention" in CFIR [30]. The diversity of professional backgrounds and training among coordinators in this study are previously demonstrated [12,[15][16][17][18]. This study indicates that the coordinators based their approach on experience from their professional background.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The need for relevant knowledge is included in the domain "characteristics of individuals" and the construct "knowledge and beliefs about the intervention" in CFIR [30]. The diversity of professional backgrounds and training among coordinators in this study are previously demonstrated [12,[15][16][17][18]. This study indicates that the coordinators based their approach on experience from their professional background.…”
Section: Discussionmentioning
confidence: 57%
“…This study contributes to the previous literature on coordination of RTW [12][13][14][15][16][17][18] by exploring facilitators and barriers across multiple levels of systems and organizations. Examples of facilitators were: a perceived advantage and positive attitudes toward coordination; an open dialogue between health care, the employee and the employer; leadership engagement and routines for the RTW process at the PCC; and collegial alliances.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations